Influence of process parameters on localized corrosion of AA7075 alloy during the production of aeronautic components. Issue 12 (14th July 2015) - Lourenço, J. C.; Faria, M. I. S. T.; Robin, A.; Prisco, L. P.; Puccini, M.C.
Abstract : The 7xxx alloys are mainly used in high stress applications, such as aircrafts structural parts, due to their great mechanical properties and low density compared to steel. Depending on the intermetallics in the alloys, they may suffer pitting which reduces the materiaĺs fatigue life time. The objective of the study was to identify what factors during the manufacture of AA7075 alloy parts are significant and how they should be controlled to minimize the occurrence of corrosion. Three steps of the production cycle were considered, machining, deburring and liquid penetrant test. After the definition of the significant factors at each step separately, a design of experiment based on a fractional factorial type was built for the whole manufacture line. The response variable was the amount of corrosion obtained by image analysis. The most significant factors were found at the machining stage: state of the bench vice jaw material (device which holds the aluminum part at the CNC lathe) and chloride concentration in the cooling fluid.